Pelatihan Model Pembelajaran Berbasis Bermain untuk Meningkatkan Perkembangan Kognitif Anak Usia Dini bagi Guru PAUD - Sri Jumiaty Permatasari; Aris Suziman; Itsnain Alfajri Husain (Prodi PGSD Unsultra, 2025)
Early childhood cognitive development is an important foundation for achieving thinking skills, understanding concepts, and solving problems in the future. Early Childhood Education (PAUD) teachers have a central role in designing learning experiences that support this development. One effective approach is a play-based learning model, which provides opportunities for children to learn through fun, contextual, and developmentally appropriate activities. This community service activity aims to improve the competence of PAUD teachers in implementing play-based learning models to optimize children's cognitive aspects. This activity is carried out through intensive training that includes delivering theory, direct practice, and joint reflection. The methods used in the training include lectures, group discussions, simulations of play activities, and preparation of lesson plans. The results of the training showed an increase in teachers' understanding and skills in designing meaningful play activities and stimulating children's cognitive development. Participating teachers were also able to develop relevant educational media and games. Based on the evaluation, more than 90% of participants stated that the training was very useful and would be applied in daily learning practices. This activity shows that practice-based and contextual training can empower PAUD teachers in presenting fun and meaningful learning for early childhood.